Risk-to-befit ratios of consecutive antidepressants for heavy menstrual bleeding in young women with bipolar disorder or major depressive disorder - Zhuo, Chuanjun; Chen, Guangdong; Lin, Chongguang; Ping, Jing; Zhu, Jingjing; Wang, Lina; Jin, Shili; Liu, Chuanxin; Zhang, Qiuyu; Yang, Lei; Li, Qianchen; Zhou, Chunhua; et al. (Frontiers in Psychiatry, 2022)
The occurrence of heavy menstrual bleeding (HMB) induced by pharmacological agents has been reported in young adult women. This study aimed to investigate a possible association between the occurrence rates of HMB and different treatment methods such as antidepressant agents alone and in combination with other pharmacological agents. The examined cohort included young women (age 18–35 years, n = 1,949) with bipolar disorder (BP) or major depressive disorder (MDD). Menstruation history for 24 months was recorded and evaluated according to pictorial blood loss assessment charts of HMB. Multivariate analyses were conducted to determine odds ratios (ORs) and 95% confidence intervals. The examined antidepressant agents had varying ORs for patients with BP vs. those with MDD. For example, the ORs of venlafaxine-induced HMB were 5.27 and 4.58 for patients with BP and MDD, respectively; duloxetine-induced HMB, 4.72 and 3.98; mirtazapine-induced HMB, 3.26 and 2.39; fluvoxamine-induced HMB, 3.11 and 2.08; fluoxetine-induced HMB, 2.45 and 1.13; citalopram-induced HMB, 2.03 and 1.25; escitalopram-induced HMB, 1.85 and 1.99; agomelatine-induced HMB, 1.45 and 2.97; paroxetine-induced HMB, 1.19 and 1.75; sertraline-induced HMB, 0.88 and 1.13; reboxetine-induced HMB, 0.45 and 0.45; and bupropion-induced HMB, 0.33 and 0.37, in each case. However, when antidepressant agents were combined with valproate, the OR of HMB greatly increased, with distinct profiles observed for patients with BP vs. those with MDD. For example, the ORs of HMB induced by venlafaxine combined with valproate were 8.48 and 6.70 for patients with BP and MDD, respectively; for duloxetine, 5.40 and 4.40; mirtazapine, 5.67 and 3.73; fluvoxamine, 5.27 and 3.37; fluoxetine, 3.69 and 4.30; citalopram, 5.88 and 3.46; escitalopram, 6.00 and 7.55; agomelatine, 4.26 and 5.65; paroxetine, 5.24 and 3.25; sertraline, 4.97 and 5.11; reboxetine, 3.54 and 2.19; and bupropion, 4.85 and 3.46, in each case. In conclusion, some antidepressant agents exhibited potential risks of inducing HMB. Therefore, a combined prescription of antidepressant agents and valproate should be carefully considered for young women with HMB.